Tradisi Literasi Al-Qur’an Anak Buruh Migran Indonesia di Sanggar Bimbingan Pantai Dalam Malaysia - Filda Amalia; Aziz Miftahus Surur (SENTRI: Jurnal Riset Ilmiah, 2026)
The tradition of Quranic literacy is an important foundation in the formation of the religious and moral identity of Muslims. However, children of Indonesian migrant workers in Malaysia face challenges in accessing Quranic education due to limited administrative identity, economic pressures, and minimal parental guidance. The absence of clear legal identity not only restricts their access to formal education but also creates a sense of marginalization that influences their motivation to seek religious literacy as a source of belonging and self-worth. This study aims to describe the Quranic literacy skills of migrant workers' children and analyze the reception and internalization of the Quranic literacy tradition in daily life at the Pantai Dalam Guidance Center in Kuala Lumpur. The study used a qualitative approach using observation, in-depth interviews, and documentation techniques. Data were analyzed through reduction, presentation, and verification using the Miles and Huberman model, and validated through triangulation of sources, techniques, and theories. The results show that Quranic literacy practices at the studio not only improve reading, writing, and memorization skills but also create a fun, interactive, and participatory learning experience. Children interpret the Quran as a source of moral values, religious motivation, and future aspirations. Reception analysis based on Ahmad Rafiq's theory emphasizes two main forms of reception: aesthetic, namely the emotional and sensory experience through tadarus and tartil; and functional/performative, where the Qur'an is carried out as a daily life practice that shapes children's attitudes, behavior, and religious identity. These findings emphasize that community-based non-formal education plays a strategic role in internalizing Qur'anic values, strengthening moral character, and building a religious and integrated migrant community.